2016
DOI: 10.1002/cssc.201600801
|View full text |Cite
|
Sign up to set email alerts
|

d‐Glucose: An Efficient Reducing Agent for a Copper(II)‐Mediated Arylation of Primary Amines in Water

Abstract: A copper-catalyzed Ullmann-type amination with primary amines in water with a combination of copper(II) triflate [Cu(OTf) ], dipivaloylmethane, and d-glucose is reported. The mild conditions and the use of an inexpensive catalyst as well as a renewable feedstock (d-glucose and the surfactant TPGS-750-M, which is derived from vitamin E) make this protocol a safe and convenient strategy for efficient C-N bond formation. This easy-to-handle procedure is extremely competitive compared to palladium-based reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 59 publications
1
20
0
1
Order By: Relevance
“…However, the use of 5 mol-% glucose strongly affected the homogeneity of the reaction mixture, allowing improved robustness, more effective stirring and an ideal processability. [19,20] Having identified CataCXium A Pd G3 as an optimal catalyst and the beneficial effect of glucose, we set out to explore the impact of the size of micelles, the amount of base, Pd/ligand ratio, and the minimal catalyst loading. Interestingly, reducing the catalyst loading to 0.50 mol-% provided a similar conversion, while the use of THF (15 vol-%) as co-solvent resulted in substantially increased reactivity and more homogeneous reaction conditions, particularly when 3.00 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of 5 mol-% glucose strongly affected the homogeneity of the reaction mixture, allowing improved robustness, more effective stirring and an ideal processability. [19,20] Having identified CataCXium A Pd G3 as an optimal catalyst and the beneficial effect of glucose, we set out to explore the impact of the size of micelles, the amount of base, Pd/ligand ratio, and the minimal catalyst loading. Interestingly, reducing the catalyst loading to 0.50 mol-% provided a similar conversion, while the use of THF (15 vol-%) as co-solvent resulted in substantially increased reactivity and more homogeneous reaction conditions, particularly when 3.00 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…Ullman couplings used for C−N bond constructions have taken a major step forward with respect to the greenness of the chemistry involved. That is, the Schmitt group has reported a remarkable observation: that Cu‐catalyzed aminations in aqueous nanomicelles composed of TPGS‐750‐M indicated that aryl bromides unexpectedly afforded better results compared to traditionally required aryl iodides . Optimization led to the appropriate ligand and base (Scheme ).…”
Section: New Cu Chemistry In Watermentioning
confidence: 99%
“…Thatis, the Schmittgroup has reported ar emarkable observation:t hat Cu-catalyzed aminations in aqueous nanomicelles composed of TPGS-750-M indicated that aryl bromides unexpectedly afforded better results compared to traditionally required aryl iodides. [51] Optimization led to the appropriate ligand and base (Scheme 26). Even more impressive is that most of these couplings can be run at room temperature ( 25 8C).…”
Section: New Cu Chemistry In Watermentioning
confidence: 99%
“…Similar results was obtained for CuFe 2 O 4 and Cu(II) salts as catalysts. Since Cu(I) is described as the possible catalytic form of copper in the catalytic cycle, by oxidative addition/reductive elimination path in similar N‐arylations, reducing agents such as sodium ascorbate (NaAsc) and D‐Glucose were used in the presence of Cu(OAc) 2 and the CuFe 2 O 4 nanoparticles. In addition, the reaction was carried out directly with Cu(I) salt: CuCl and CuI Regardless of the initial copper source, the reaction proceeds with the same conversion and slight differences in selectivity (Table ).…”
Section: Figurementioning
confidence: 99%